PREVALENCE OF BALANTIDIUM SP. INFECTION IN SWAMP BUFFALOES USED IN THE MAKEPUNG TRADITION IN JEMBRANA REGENCY, BALI - Akilah Balkis; I Made Dwinata; Ida Bagus Made Oka (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Buffaloes play an essential role in society, both as a food source and in socio-cultural aspects. One tradition involving buffaloes is Makepung in Jembrana Regency, Bali, which requires the buffaloes to be in optimal health. Gastrointestinal parasitic infections, such as Balantidium sp., can affect buffalo health and pose zoonotic risks. This study aims to determine the prevalence of Balantidium sp. infection in Makepung buffaloes and analyze the factors associated with its prevalence, including age, management practices, and geographical region. This research employs an observational method with a cross-sectional study design. A total of 120 male Makepung buffaloes from three districts in Jembrana Regency Melaya, Negara, and Mendoyo were selected using purposive sampling. Fecal samples were collected and examined using a modified sedimentation method to detect Balantidium sp. presence. Data were analyzed descriptively, and relationships between variables were tested using the Chi-square test. The results showed that the prevalence of Balantidium sp. infection in Makepung buffaloes was 45.8%. Geographical region and feed source significantly influenced infection prevalence (P<0.05), whereas age and management factors, such as housing system, and cleanliness, did not show significant effects (P>0,05). Makepung buffalo farmers are advised to improve sanitation, improve drainage, separate the enclosures, and use antiprotozoal drugs under the supervision of a veterinarian to prevent Balantidium sp. infections and resistance.